Molecular species identification of processed sea cucumbers from selected Malaysian markets using COI MtDNA gene - Kamarudin, Kamarul Rahim; Mohamed Rehan, Aisyah; Mohd Noor, Hanina; Ramly, Nur Zazarina; Mohamed Rehan, Maryam (2015)
This study aimed to determine species identities of processed sea cucumbers from selected Malaysian markets i.e. Kuantan, Pahang (East Coast region of Peninsular Malaysia) and Langkawi Island, Kedah (the Northern region) in the forms of dried (seven specimens) and frozen (12 specimens) products. Most of the products were not labelled with species details. Fresh samples that were morphologically identified as Stichopus horrens (gamat species– three specimens) and Holothuria leucospilota (timun laut species– three specimens) from Pangkor Island, Perak were also included as reference samples. Partial sequences of proteincoding cytochrome c oxidase I (COI) mitochondrial DNA (mtDNA) gene were acquired, and subsequent analyses using Basic Local Alignment Search Tool (BLAST) and phylogenetic analyses were done. Phylogenetic analyses were incorporated to understand genetic relationship of the sea cucumber species and to compare the sequences from processed sea cucumber with the species and source details of the products. Phylogenetic analyses of 25 partial sequences using five main methods namely Neighbour-Joining (NJ), Maximum Likelihood (ML), Minimum Evolution (ME), Unweighted Pair Group Method with Arithmetic Mean (UPGMA) and Maximum Parsimony (MP) showed the presence of two main families of sea cucumbers: Stichopodidae (gamat family) and Holothuriidae (timun laut family), thus supporting the BLAST results. Specimens of S. horrens and S. herrmanni were the two gamat species that clustered under family Stichopodidae. A specimen of H. leucospilota, the most dominant species from family Holothuriidae in Malaysia, was also recorded. Further studies with more samples and mtDNA genes e.g. non-protein-coding 16S mtDNA gene need to be done to get a better view and verification. The outcomes of this study will provide better information on the level of species substitution and product mislabelling issues of processed sea cucumbers in Malaysian markets which will subsequently assists the enforcement agencies to monitor and overcome the issues through mtDNA sequencing technique.